Don’t Be Afraid to Change: a Study of Mediation Variables - Sulistiyani, Endang; Hermawan, Iwan; Anuar, Aimi; Ayuwardani, Mellasanti; Nugroho, Bayu Setyo; Rosinda Siagian, Stefani Mutiara (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2023)
This study aims to determine the antecedent variables that affect business performance and to determine the role of the readiness to change a variable in mediating the relationship between managerial work efficacy and business performance. The object of this research is the tour travel business in Central Java. The sample of this research is the director of each research object as the main leader and decision maker in dealing with the Covid-19 pandemic situation and the new normal era. Methods of data collection by distributing questionnaires, interviews, observation, and literature study. The sampling method used purposive sampling. Data analysis using Structural Equation Modeling technique. Based on statistical results, the direct effect of managerial work efficacy is not significant on business performance. The indirect effect of managerial work efficacy on business performance through readiness to change shows significant results. The results of the role test show that readiness to change can mediate the relationship between managerial work efficacy and business performance..